2017
DOI: 10.1080/02640414.2017.1280180
|View full text |Cite
|
Sign up to set email alerts
|

Development, implementation and assessment of a concussion education programme for high school student-athletes

Abstract: Although experts have noted that adolescent athletes should be educated about concussions to improve their safety, there is no agreement on the most effective strategy to disseminate concussion education. The purpose of this study was to develop, implement and assess a concussion education programme. More precisely, four interactive oral presentations were delivered to high school student-athletes (N = 35, M = 15.94, SD = 0.34) in a large urban centre. Participants completed a questionnaire at three time-point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 38 publications
3
43
0
Order By: Relevance
“…Overall, there still remains a clear barrier in that many athletes are simply not motivated to report symptoms of concussion. When educational efforts about concussion safety are directed at the athletes themselves, one study reported an increased desire to avoid collisions, but behaviors for reporting concussions that occur may still be unchanged (21). Indeed, many athletes want to play despite any potential cost to their own health, an attitude which creates ethical conflicts between the needs of the player, the needs of the team, and the goals of the medical community (22).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there still remains a clear barrier in that many athletes are simply not motivated to report symptoms of concussion. When educational efforts about concussion safety are directed at the athletes themselves, one study reported an increased desire to avoid collisions, but behaviors for reporting concussions that occur may still be unchanged (21). Indeed, many athletes want to play despite any potential cost to their own health, an attitude which creates ethical conflicts between the needs of the player, the needs of the team, and the goals of the medical community (22).…”
Section: Discussionmentioning
confidence: 99%
“…The CKI-subscale in this study showed good internal consistency (Cronbach's α = .82) and the CAI-subscale showed acceptable internal consistency (Cronbach's α = .71). The RoCKAS-ST has been described extensively in the literature, and further details on the measure can be found in Caron et al (8).…”
Section: Concussion Knowledge and Attitudesmentioning
confidence: 99%
“…Motorsport-specific contextualization, examples, and case studies were created through discussions with expert stakeholders. While being tailored to motorsport, the fundamental concepts within the area of concussion were covered (1,8). Workshop 1 covered: the definition of concussion; mechanisms of injury; signs and symptoms of concussion; basic pathophysiology; the physical, psychological and emotional impact of concussions and the potential short-and long-term effects on health and wellbeing as well as sport performance.…”
Section: Workhop-programme Structure and Contentmentioning
confidence: 99%
See 2 more Smart Citations